Patterns of human-wildlife conflict and management implications in Kenya: A national perspective. Issue 2 (3rd March 2020) - Long, Huaping; Mojo, Dagne; Fu, Chao; Wang, Guoqin; Kanga, Erustus; Oduor, Ayub M. O.; Zhang, Linxiu
ABSTRACT: With the intention to augment better management of human-wildlife conflicts (HWC) in Kenya, we assessed a national HWC pattern using a decade-long (2005–2016) monitoring data series. The results demonstrate that out of 29, 647 reported HWC cases, crop raiding was the most frequent type (73%) followed by livestock depredation (23%) and infrastructure damage (4%). Different crops, livestock and wildlife species involved in the conflicts were also identified. Although HWC cases were reported from all the 47 counties that make up Kenya, about 75% of the incidences occurred in 10 counties, with the highest number of cases being in Taita Taveta County. Human-wildlife conflicts exhibited variations across the seasons and years. Overall, from the HWC cases reported, the number of crop raiding incidences decreased, livestock depredation increased, while property damage was constant. We suggest counties that experienced most HWC cases should be given a priority when implementing measures to mitigate HWC.